BOOST CONVERTER DESIGN FOR ELECTRIC WHEEL CHAIR CHARGING STATION WITH SOLAR PANEL SOURCE: RANCANG BANGUN BOOST CONVERTER UNTUK CHARGING STATION KURSI RODA LISTRIK DENGAN SUMBER SOLAR PANEL - Mahendra, Moh. Rifqi (Techno Bahari, 2022)
Public facilities must support electric wheelchair users which of course must refer to the Sustainable Development Goals (SDGs) of clean and affordable energy. The solar panel-based charging station will assist users in charging electric wheelchair batteries. Users are expected to no longer worry about the battery running out in the electric wheelchair when outside the home and the battery adjusts from the electric wheelchair, which is 25.9V 6000mAh. The research method used is by utilizing solar panels as a source to charge the battery. From the solar panel source, the voltage and current will be read using a voltage sensor, where the voltage sensor will read the Analog Digital Converter (ADC) value through the ArduinoUNO microcontroller to convert the value, the voltage coming out of the solar panel is used for charging with a boost converter. when the voltage that comes out of the solar panel is known, the battery will charge with a constant voltage of no more than 32.4V. The battery charging circuit uses a boost converter circuit. The charging process is carried out until the battery is fully charged at a voltage of 29.4V, after the charging process is carried out to a voltage of 29.4V, the integration of charging control with the BMS monitors the State of Charge when it is full, the charging is disconnected so that there is no overcharging to the battery and can minimize damage to the battery